ADAPTIVE SELECTION OF NEURAL NETWORKS FOR A COMMITTEE DECISION - Lipnickas, Arunas; Korbicz, Jozef (International Journal of Computing, 2014)
To improve recognition results, decisions of multiple neural networks can be aggregated into a committee decision. In contrast to the ordinary approach of utilising all neural networks available to make a committee decision, we propose creating adaptive committees, which are specific for each input data point. A prediction network is used to identify classification neural networks to be fused for making a committee decision about a given input data point. The jth output value of the prediction network expresses the expectation level that the jth classification neural network will make a correct decision about the class label of a given input data point. The proposed technique is tested in three aggregation schemes, namely majority vote, averaging, and aggregation by the median rule and compared with the ordinary neural networks fusion approach. The effectiveness of the approach is demonstrated on three well known real data sets and also applied to fault identification of the actuator valve at one sugar factory within the DAMADICS RTN.